ChemInform Abstract: Thermal Reactions Involving 1‐Azadienes and Allenic Esters‐(II): Reactions of 3‐(N‐Aryliminomethyl)chromones with Allenic Esters—Tandem Reorganization of [2 + 2] Cycloadducts to Novel Compounds. Issue 47 (November 2015) - Kapur, Ashish; Sharma, Vishal; Kaur, Amandeep; Parashar, Poonam; Kanwal, Priyanka; Gupta, Vivek; Ishar, Mohan Paul S.
Abstract: The course of the title reaction depends on the substituents on the allenic esters providing three different types of aromatic ketones.